Perlindungan Hukum Terhadap Karya Cipta Di Media Internet - AR, Azhari (Universitas Islam Sumatera Utara, 2023)
The legal aspect becomes very important because the law is expected to be able to overcome various problems that arise related to IPR. The law must be able to provide protection for a person's intellectual work, so that it is able to develop the creative power of society which ultimately leads to the goal of protecting IPR. In addition, the technological aspect is also one of the factors that becomes very dominant in the development and protection of IPR. Protection of Copyright as Movable Objects That Have no Form, that Copyright is an intangible movable object in accordance with what is stipulated in Article 16 Paragraph (1) UUHC. Copyright as an intangible movable object in the conception of civil law is a material property right over an immovable object.Keywords : Legal Protection, Copyright, Internet Media